Sikap Etis Manajer terhadap Praktik Earnings Management - Se Tin . (Universitas Kristen Maranatha, 2007)
This study examines the ethical judgment of managers on various dimensions of earnings management practices. This study hypothesizes that different types, materiality, periodsof effect, consistency with generally accepted accounting principles, directions, and objectives of earnings management does not have effects on managers ethical judgment. The results, based on responses from managers studying at master of management program, Parahyangan Catholic University, Maranatha Christian University, Padjajaran University and Widyatama University, show that the types, materiality,period of effect of earnings management, a consistency with generally accepted accounting principles and directions have eflects on the ethical judgment of the managers on the practices. on the other hand, objectives of earnings management does not have eflect on the judgment.Keywords : Earnings management, ethical judgment